Ability of organizational commitment and emotional intelligence moderating effect of role stress on turnover intention - Dwiputra, I Made Arya; Astika, Ida Bagus Putra (International research journal of management, IT and social sciences, 2019)
This research was conducted to obtain empirical evidence of the influence of role stress on turnover intentions of tax consultants in Tax Consultant Offices in Bali Province with organizational commitment and emotional intelligence as moderating variables. This research was conducted at 35 Tax Consultant Offices in Bali Province. The research sample was determined by purposive sampling method and based on the specified criteria obtained a total sample of 185 respondents. Data collection is done using the questionnaire method. The hypothesis is tested using simple regression analysis techniques and the Moderating Regression Analysis (MRA). The results showed that role stress had a significant positive effect on turnover intentions. Organizational commitment and emotional intelligence show weakening the positive influence of role stress on turnover intentions.